“And the Earth Was Still Moving…” The Massacre of Jews in Szczeglacin in Eyewitness’ Testimonies - Marta Woźniak (Zagłada Żydów)
The article deals with a labor camp for Jews founded by the Germans in Cerkwisko near Bartków Nowy, Karczew Commune, was transferred to the village of Szczeglacin due to the works’ advancement along the river. The Jews who died in that camp performed work connected with water management which consisted in draining the farmland and engineering the Kołodziejka River a Bug tributary. The liquidation of the Szczeglacin camp probably took place in the morning of 22 October 1942.  Several hundred Jews were killed with a primitive tool – a wooden club. According to the witnesses, “when spring came,” probably of 1944, the Germans returned to the spot to conduct an exhumation of the remains in order to ultimately cover the traces. The article is based on various sources – from oral accounts, collected in 2009 in Szczeglacin and the neighboring villages, through records produced in 1947  (Josek Kopyto’s testimony) and 1994e manuscript of a peasant from Bartków Stary as well as regional publications